Islam beyond the differences [videorecording] - Sheikh Yusuf Estes; One Islam Production; ICRA Youth Centre, Inc.; Saba Islamic Media ([Australia] : One Islam Production ; Kuala Lumpur : Saba Islamic Media (distributor), 2004)
The speaker talk about the concept of ethmology and the differences of Islam and others and beyond that. Difference in culture, age, language, status of living and all kind of differences. Also talk about the Islam generally
Title from title screen
Speaker: Sheikh Yusuf Estes
Keywords: Religious life -- Islam; Islam